2017
DOI: 10.24912/ja.v21i3.267
|View full text |Cite
|
Sign up to set email alerts
|

Peran Corporate Governance Dalam Menurunkan Kebangkrutan Pada Perusahaan Di Indonesia

Abstract: This research examines the influence of Corporate Governance on FirmPerformance measured by Tobin's Q and Financial Distress measured by Z-score. The samples used were 72 companies engaged in the manufacturing industry are listed on the Indonesia Stock Exchange (BEI) for five years from 2011 to 2015. The analytical methods used in this research is panel data regression, discriminant analysis, and logistic regression. The results showed that (1) there is no significant impact between corporate governance practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Studies that used GCG as variable are Dianova and Nahumury (2019), Hilaliya and Margaretha (2017), Juniarti (2013), Cahyani and Diantini (2016), and others. Next, the studies that used liquidity, profitability, leverage, and activity as variables are Nurfajrina et al (2016), (Heniwati and Essen (2020), Pujiastuti and Yuharningsih (2014), Oktarina (2017), Utami and Kartika (2019), Sumani (2019), Antikasari and Djuminah (2017), and (Mafiroh and Triyono (2018).…”
Section: Table 4 Articles Distributions Based On Internal Factor Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that used GCG as variable are Dianova and Nahumury (2019), Hilaliya and Margaretha (2017), Juniarti (2013), Cahyani and Diantini (2016), and others. Next, the studies that used liquidity, profitability, leverage, and activity as variables are Nurfajrina et al (2016), (Heniwati and Essen (2020), Pujiastuti and Yuharningsih (2014), Oktarina (2017), Utami and Kartika (2019), Sumani (2019), Antikasari and Djuminah (2017), and (Mafiroh and Triyono (2018).…”
Section: Table 4 Articles Distributions Based On Internal Factor Variablesmentioning
confidence: 99%
“…It could be seen from the many studies done in Indonesia about this topic. Some examples of studies in Indonesia about financial distress are as follows: The Role of Corporate Governance in Reducing Bankruptcy in Companies in Indonesia (Hilaliya and Margaretha, 2017), Analysis of Financial Ratios and Measures, Predictions of Financial Distress, and Investor Reactions (Vestari and Farida, 2013), Predicting Financial Distress with Telecommunication Company Binary Logit Regression (Antikasari and Djuminah, 2017), Antecedents of Probability of Financial Distress in Manufacturing Companies in Indonesia (Pujiastuti and Yuharningsih, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, these results were not consistent with the research of Christine et al [12] and Yudhistira [10] who suggested that profitability had a significant positive effect on financial distress. While other studies have found different results, namely leverage had no effect on financial distress [18] .…”
Section: Introductionmentioning
confidence: 67%
“…The existence of corporate governance can overcome agency problems between company owners and managers. As in research Hilaliya & Margaretha, (2017) concluded that the corporate governance index negatively and significantly affects financial distress. This indicates that if corporate governance is implemented properly, the possibility of financial distress can decrease, while research from Yuliani & Rahmatiasari, (2021) concluded that corporate governance has a positive and significant effect on financial distress, due to supervision that can improve per-formance.…”
Section: The Effect Of Corporate Governance On Financial Distressmentioning
confidence: 97%